The Influence of Personal Protective Equipment (PPE) Usage, Age, Work Tenure on Workplace Accidents - Ichtiary Shinta Sabrina; Winarko; Pratiwi Hermiyanti; Suprijandani; Muhammad Agus Ainur Rosyid (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2024)
Workplace accidents can reduce productivity, which occurs as a result of unsafe actions and unsafe conditions in the Small and Medium Enterprises (SMEs) of leather tanning in Magetan. Workplace accidents could be caused by workes low awareness of wearing Personal Protective Equipment (PPE), as well as factors like age and work tenure on workplace accidents in the leather tanning SMEs in Magetan 2024. The research design employed an observational analytic method with a Cross-Sectional approach. The sample size consisted 66 people out of a population of 190, selected through proportional random sampling. The variables of PPE use, age, and work tenure, which were collected through observation and interviews, were then processed and analyzed using the Spearman Correlation statistical test (r2). The results indicated that the use of PPE, including masks,gloves, and boots, was at 36,4%, the proportion of workers aged over 30 years was 54,5%, and those with a work tenure over 5 years was 59,1%. The analysis showed that PPE use (p=0.000) and age (p=0.035) had an impact on workplace accidents, with a correlation value of p=0.232 more than 0.05. The study concluded that the use of PPE and the age of workers in the leather tanning SMEs in Magetan influenced workplace accidents. It is recommended that management provide complete PPE such as masks, boots, gloves and conduct regular monitoring of PPE use conditions. Additionally, workers should use PPE according to standars while performing their duties.